SUPER PREDICTOR FOR THE INDIAN PREMIER LEAGUE - Rachit Mehul Pathak (Innovative Research Thoughts, 2023)
I decided to work on the Super Predictor for The Indian Premier League and my main objectives was to calculate and tell which factors are majorly crucial and of higher significance for predicting the outcome of a game. Factors such as Most Matches Played In (Stadiums), Most Winning Team in Each Season, Top 5 Teams by win-rate, Net run rate of a team across various seasons, Wins by Batting First / Second, Matches Won After Toss Win, Player with Most Awards and On-Field Umpire with Maximum Matches were considered.